2021
DOI: 10.1080/21655979.2021.1961662
|View full text |Cite
|
Sign up to set email alerts
|

Interplays of enzyme, substrate, and surfactant on hydrolysis of native lignocellulosic biomass

Abstract: Tracking enzyme, substrate, and surfactant interactions to reach maximum reducing sugar production during enzymatic hydrolysis of plant biomass may provide a better understanding of factors that limit the lignocellulosic material degradation in native rice straw. In this study, enzymes (Cellic Ctec2 cellulase and Cellic Htec2 xylanase) and Triton X-100 (surfactant) were used as biocatalysts for cellulose and xylan degradation and as a lignin blocking agent, respectively. The response surface model (R 2 = 0.99 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…On the other hand, ionic surfactants can have a negative effect on the enzymatic hydrolysis of cellulose. Lee et al (2021) found that the rate of hydrolysis decreased by 36%, 38%, and 50% in the presence of amphoteric, anionic, and cationic surfactants, respectively. This decrease in hydrolysis rate could be due to the surfactant interfering with the enzyme's ability to bind to the cellulose substrate (Lee et al 2021).…”
Section: Surfactant Effectmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, ionic surfactants can have a negative effect on the enzymatic hydrolysis of cellulose. Lee et al (2021) found that the rate of hydrolysis decreased by 36%, 38%, and 50% in the presence of amphoteric, anionic, and cationic surfactants, respectively. This decrease in hydrolysis rate could be due to the surfactant interfering with the enzyme's ability to bind to the cellulose substrate (Lee et al 2021).…”
Section: Surfactant Effectmentioning
confidence: 98%
“…Lee et al (2021) found that the rate of hydrolysis decreased by 36%, 38%, and 50% in the presence of amphoteric, anionic, and cationic surfactants, respectively. This decrease in hydrolysis rate could be due to the surfactant interfering with the enzyme's ability to bind to the cellulose substrate (Lee et al 2021). Therefore, based on the available information, nonionic surfactants seem to be more effective in enhancing the enzymatic hydrolysis of cellulose.…”
Section: Surfactant Effectmentioning
confidence: 98%
“…To perform the hydrolysis of cellulose and hemicellulose, commercial enzymatic cocktails, such as Cellic CTec (cellulase) and Cellic HTec (xylanase) families, have emerged. The Cellic CTec cocktail stands out for having high βglucosidase activity in its composition, making it the protagonist in the production of reducing sugars in the process of bioethanol production (Lee et al 2021;Triwahyuni et al 2015). In addition, the Cellic HTec cocktail has excellent endoxylanase activity and selectivity for soluble hemicellulose, contributing to the hydrolysis of lignocellulosic materials into fermentable sugars.…”
Section: Enzymes Used In the Hydrolysis Of Lignocellulosic Biomassmentioning
confidence: 99%
“…Presumably, the presence of surfactant can ease the detachment of enzyme from such sites, thereby allowing it to be more effective in its enzymatic activity (Wang et al 2013;Fritz et al 2015). However, this mechanism has been called into question by some recent work (Lee et al 2021).…”
Section: Enzymatic Actionmentioning
confidence: 99%